Implementasi Modul LoRa dan GPS untuk Efisiensi Pengumpulan Sampah - Rifai, Ahmad; Octariano, Andafa Eka; Wagyana, Agus; Damas Srihantaran, Omar Rais (Politeknik Negeri Jakarta, 2023)
One of the issues that is still prevalent in Indonesia is garbage accumulation. This is a result of low public awareness about trash management. Inefficient waste management damages people's health and the area's natural attractiveness. Digital technology and information implementation can help with waste collection management. Low power transmission capabilities are provided by the 2015 version of the Long Range (LoRa) communication protocol. This study creates a LoRa-enabled Smart Garbage Collection system to assist with waste management. GPS module and ultrasonic sensors are used in the construction of the Smart Garbage Collection system. Through the LoRa communication system, the measurement data from the sensors and modules is transmitted to the receiver via the LoRa module. The LoRa point-to-point technique is employed. The Received Signal Strength Indicator (RSSI) is the metric that is examined in LoRa. It should be simpler with this method to keep an eye on the trash can's capacity and to get the coordinates of its location using a LoRa receiver. The test results show that this system has an error percentage of less than 8%, a radius of up to 280 meters, and an RSSI value of -121 dBm in non-line of sight (NLOS).